Extraction of phenolic compounds from palm oil processing residues and their application as antioxidants - Tsouko, Erminda (Array, 2019)
The side streams derived from the palm oil production process, namely palm kernel cake, palm pressed fibre, palm kernel shells and empty fruit bunches, were evaluated as sources of phenolic compounds. Among these streams, kernel cake had the highest total phenolic content (in mg of gallic acid equivalents (GAE) per g of dry sample) with a value of 5.19, whereas the empty fruit bunches had the lowest value (1.79). The extraction time and liquid-to-solid ratio were investigated to optimize the phenolic extraction. Kernel cake exhibited the highest total phenolic content (5.35 mg/g) with a liquid-to-solid ratio of 40:1 during 20 min of extraction. The main phenolic compounds of the extracts deriving from all byproduct streams were also identified and quantified with HPLC-DAD. Pyrogallol, 4-hydroxybenzoic acid, gallic acid and ferulic acid were the main compounds found in kernel cake extracts. Empty fruit bunch and pressed fibre extracts were also rich in 4-hydroxybenzoic acid, while pyrogallol was the predominant compound in kernel shell extracts. All extracts showed antioxidant activity as it was indicated from the results of DPPH analysis and subsequently tested in sunflower oil aiming to prolong its shelf life. The addition of 0.8 % kernel cake extract increased the induction time of sunflower oil more than 50 %. According to the results obtained in this study, kernel cake extracts could be considered as a value-added co-product with a potential application as antioxidants in the food industry.